2015
DOI: 10.1186/s12917-015-0473-y
|View full text |Cite
|
Sign up to set email alerts
|

Canine mammary cancer cells direct macrophages toward an intermediate activation state between M1/M2

Abstract: BackgroundCanine mammary carcinoma is the most common cancer in female dogs and is often fatal due to the development of distance metastasis. The microenvironment of a tumour often contains abundant infiltrates of macrophages called tumour-associated macrophages (TAMs). TAMs express an activated phenotype, termed M2, which sustains proliferation of cancer cells, and has been correlated with poor clinical outcomes in human cancer patients. Cancer cells themselves have been implicated in stimulating the conversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 32 publications
(50 reference statements)
0
26
0
2
Order By: Relevance
“…TAMs in canine mammary cancer have already been associated, by our group, with skin ulceration, histological type, nuclear grade, tubular differentiation, and decrease in overall survival [56]. Similarly to human breast cancer, in canine mammary cancer the macrophages also polarize toward the M2 phenotype [57]. Recently, we and others demonstrated that TAM infiltration is significantly associated with VEGF expression in malignant canine mammary tumors and that genes involved in angiogenic cellular pathways have been significantly upregulated in macrophages cocultured with canine mammary tumor cell lines [20, 58].…”
Section: Inflammatory Cells and Sustained Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…TAMs in canine mammary cancer have already been associated, by our group, with skin ulceration, histological type, nuclear grade, tubular differentiation, and decrease in overall survival [56]. Similarly to human breast cancer, in canine mammary cancer the macrophages also polarize toward the M2 phenotype [57]. Recently, we and others demonstrated that TAM infiltration is significantly associated with VEGF expression in malignant canine mammary tumors and that genes involved in angiogenic cellular pathways have been significantly upregulated in macrophages cocultured with canine mammary tumor cell lines [20, 58].…”
Section: Inflammatory Cells and Sustained Angiogenesismentioning
confidence: 99%
“…Evidences from clinical and experimental studies indicate that macrophages are versatile cells that are capable of displaying different functional activities in order to promote breast cancer progression and metastasis [20, 120, 121]. TAMs polarization in mammary tumor sites are modulated by the tumor microenvironment and these cells are “educated” adopting a role that facilitates angiogenesis, matrix breakdown, and tumor cell motility in a COX-2-dependent manner [71, 105].…”
Section: Inflammatory Cells and Cancer Cell Biomarkersmentioning
confidence: 99%
“…The cell concentration was adjusted for 5×10 4 cells/mL to vaccinate 96-well plates, each well 180 µL. With RPMI1640 medium dissoluted, (1, 3, 5, 7, 9 nmol/L) antisense oligonucleotides were joined every well for 44 h, and 20 µL MTT (5 mg/mL) was added to cultivate for 4 h, then 200 uL DMSO was added.…”
Section: M-csf-specific Antisense Oligonucleotidementioning
confidence: 99%
“…The three kinds of HeLa cells (1x10 4 per well) were cultured in 96-well plates. Thereafter, 20 µL MTT solution was added to each well.…”
Section: Cell Proliferation Assaymentioning
confidence: 99%
See 1 more Smart Citation